The Marketing Communication Strategy For The Home-Batik Industry: Between Challenges And Opportunities - Ladini, Idfi Eva; Khumayah , Siti; Erawati, Dedet (Jurnal Ekuisci, 2025)
Background. Batik is an intangible cultural heritage of Indonesia, recognized by UNESCO in 2009 and widely recognized worldwide. The batik industry today focuses not only on preserving ancestral cultural heritage, but also on a highly valuable commodity that deserves to be preserved. Besides its economic value, batik also serves as a symbol, icon, and cultural identity that enhances the nation's competitiveness internationally, including home-based batik industries spread across various regions in Indonesia, one of which originates from Trusmi Village, Cirebon Regency, West Java. However, the batik industry faces various challenges, including limited capital, market access, distribution, and a lack of understanding of effective marketing communication strategies, particularly in utilizing digital platforms. Aims. This study aims to analyze the opportunities and challenges associated with implementing marketing communication strategies for the home-based batik industry. Methods. By using a qualitative approach and supported by the use of Integrated Marketing Communication (IMC) Theory and Relationship Marketing in analyzing the findings in the field, the results of the study indicate that social media, the TikTok platform, is a strategic tool to promote batik products, especially those originating from home-based batik artisans, widely to both domestic and international audiences using interesting and consistent content. Result. The results of this study suggest that artisans consistently and continuously build customer loyalty. Implementation. Additionally, artisans must also develop and strengthen a good and attractive brand image and branding.